Inhibiting Factors of Dance Learning in the Higher Grades of Elementary School Students - Da Ary, Deasylina; Markamah (Universitas Pendidikan Ganesha, 2024)
The dance learning process in elementary schools’ experiences imbalances with the demands of the applicable curriculum. In reality, dance learning has not been paid attention to by various parties so that students do not get the opportunity to develop creativity and imagination in dance movements. This research aims to analyze the factors inhibiting dance learning among high grade students in elementary schools in depth. This research includes descriptive qualitative research that uses a case study approach. Data collection techniques through interviews, observation and documentation. Data validity techniques include triangulation of sources and techniques. The data analysis technique used is the Miles and Huberman model. The results of this research indicate that the implementation of dance learning for high class students in elementary schools is still not optimal because there are inhibiting factors in various aspects, including the school, curriculum, school policies, facilities, infrastructure, class management, students, teachers, environment, and society's perception regarding dance learning, so that students' basic development becomes stagnant. The results of this research can be input for various parties to increase collaboration in order to improve the quality of learning in a more progressive direction than before.